PROPORTIONAL REPRESENTATION AND PREFERENCES VS. GENDER EQUALITY. THE CASE OF USHUAHIA LEGISLATURE, A SMALL DISTRICT (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
In the city of Ushuaia there were several intents to change or to eliminate the method of preferences for the legislators in order to guarantee gender equality among the representatives. It has been said that, erasing this method or changing it would be a good measure in order to concrete gender equality in the legislature. We aim to present here an historical evolution of the voting system to see if it is true or if, on the contrary, due to other causes, there should be other issues to think about.
Keywords: Electoral system; gender equality; Ushuaia; evolution